Scrolling Toward Simplicity: Social Media Use, Fear of Missing Out, and Minimalist Consumption Among Generation Z In Indonesia - Mutiarasari, N. Azizia Gia; kiswardhani, Wahyu Eka; Aditasari, Krisnayanti (Jurnal Ilmiah Manajemen & Bisnis, 2025)
This study examines how social media use and fear of missing out (FoMO) relate to minimalist consumption tendencies among young people in Indonesia. The study examines whether intense social media use merely stimulates overconsumption or can also support a more focused and sustainable minimalist lifestyle. A cross-sectional quantitative survey was conducted with 275 young Indonesian users who actively use Instagram and TikTok. Data were collected through an online questionnaire and analyzed using partial least squares structural equation modeling (PLS-SEM) to test for direct and indirect effects. Results indicate that social media use has a positive and significant effect on FoMO and a positive and significant effect on minimalist consumption. Conversely, FoMO does not significantly predict minimalist consumption; therefore, FoMO does not mediate the relationship between social media use and minimalist consumption. These findings suggest that social media can serve as a supportive space for minimalist practices when users are exposed to content and communities that promote simple and sustainable living. Practically, despite the insignificant role of FoMO, this study informs sustainable marketing and consumption initiatives by suggesting that brands and their supporters integrate buy less but better messaging into Instagram/TikTok campaigns, encourage mindful reordering and purchasing routines, and build community based engagement rather than relying on promotional cues driven by urgency or FoMO. Overall, this study highlights the ambivalent role of social media in youth consumption behavior and suggests opportunities to promote minimalist lifestyles in developing countries.